2018
DOI: 10.1508/cytologia.83.149
|View full text |Cite
|
Sign up to set email alerts
|

A Report on Classical Cytogenetics of Hihgfin Barb Fish, <i>Cyclocheilichthys armatus</i> (Cypriniformes, Cyprinidae)

Abstract: Conventional staining and Ag-NORs banding techniques were applied on the chromosomes of hihgfin barb fish, Cyclocheilichthys armatus. Specimens were collected from the Chao Phraya River, Thailand. The mitotic chromosome preparations were directly obtained from kidney tissues of eight males and eight females. The results revealed that the diploid chromosome numbers of C. armatus was 2n=50 and the fundamental number (NF) was 94 in both males and females. The karyotype consists of four large metacentric, six larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 27 publications
(23 reference statements)
10
16
1
Order By: Relevance
“…"Osteochilini" species possess 2n = 50 (Arai, 2011), which is also considered a basal pattern for cypriniform fishes (Chaiyasan et al, 2018). Our results showed that 2n = 50 is also a demonstrably conserved pattern for all Osteochilus species karyotyped to date.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…"Osteochilini" species possess 2n = 50 (Arai, 2011), which is also considered a basal pattern for cypriniform fishes (Chaiyasan et al, 2018). Our results showed that 2n = 50 is also a demonstrably conserved pattern for all Osteochilus species karyotyped to date.…”
Section: Discussionsupporting
confidence: 61%
“…“Osteochilini” species possess 2n = 50 (Arai, 2011), which is also considered a basal pattern for cypriniform fishes ( Chaiyasan et al. , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The single NOR-bearing chromosomes in the C B A present result are most likely homologous to that observed in Sphoeroides greeleyi (Brum et al 1995) and S. testudineus (Sá-Gabriel and Molina 2005). A single NORbearing chromosome is a common characteristic found in many fish groups as well as vertebrates (Supiwong et al 2010, 2012a,b, 2013b, Chooseangjaew et al 2017Kasiroek et al 2017;Phimphan et al 2017;Sangpakdee et al 2017;Chaiyasan et al 2018). NOR mapping is frequently used to compare variations, as well as to identify and explain speciation.…”
Section: Discussionmentioning
confidence: 99%
“…After that, slides were soaked in distilled water until the coverslips were separated. The slide was stained with 20% Giemsa's solution for 1 min (Sangpakdee et al 2017, Chaiyasan et al 2018.…”
Section: Chromosome Stainingmentioning
confidence: 99%
“…In Thailand, including Indochina and the northern Malay peninsula, Alongklod Tanomtong and coworkers have recently focused on fish karyotype analysis and have published 15 reports in Cytologia over the last 2 years on the following fish species: Humpback cardinalfish, Fibramia lateralis (Kasiroek et al 2017a); Banggai cardinalfish, Pterapogon kauderni (Kasiroek et al 2017b); triangle butterflyfish, Chaetodon triangulum and yellow butterflyfish, C. andamanensis (Supiwong et al 2017a); Indian vagabond butterflyfish, Chaetodon decussatus and Lined butterflyfish, C. lineolatus (Supiwong et al 2017b); Nile tilapia, Oreochromis niloticus (Sriuttha et al 2017); three-spot damselfish, Dascyllus trimaculatus (Getlekha et al 2017); ocellated dragonet, Synchiropus ocellatus and picturesque dragonet, S. picturatus (Kasiroek et al 2017c); crystal eye catfish, Hemibagrus wyckii (Supiwong et al 2017d); Chevey s sheetfish, Micronema cheveyi (Pinthong et al 2017); F 1 hybrid catfish: Mekong giant catfish, Pangasianodon gigas striped catfish, P. hypophthalmus and spot pangasius, Pangasius larnaudii Pangasianodon hypophthalmus (Sreeputhorn et al 2017); whitecheek monocle bream, Scolopsis vosmeri (Supiwong et al 2017c); snakehead fishes, Channa marulius and C. marulioides (Sarasan et al 2018); Hihgfin barb fish, Cyclocheilichthys armatus (Chaiyasan et al 2018); black lancer, Bagrichthys majusculus (Supiwong et al 2018); and longfin carp, Labiobarbus leptocheilus (Saenjundaeng et al 2018).…”
Section: Post-war Trajectory and A New Ichthyologic Trendmentioning
confidence: 99%